Seed system of Pakistan: Policy challenges and prospects - Rana, Abdul Wajid; Gill, Sitara; Akram, Iqra (International Food Policy Research Institute, 2022)
The seed industry in Pakistan has undergone significant developments since the 1950s and has transitioned from ‘Green Revolution’ to ‘Gene Revolution’. The 2015 amendment in the Seed Act, 1976, and the enactment of Plant Breeders’ Rights Act and Rules have provided long awaited intellectual property protection for proprietary seed. Notwithstanding this fundamental change, the challenge of effective enforcement of intellectual property rights remains. This paper presents how the seed industry has evolved over the years through evaluating the regulatory and institutional framework along with looking into the major challenges that still plague the seed system of Pakistan. It also explores how the private sector can be incentivized to invest in the seed sector while protecting the farmers’ rights. Findings reveal that there seems to be a lot of scope for strengthening the seed system of Pakistan via encouraging private sector participation mainly through developing proactive markets with strong institutional mechanism along with scientific and time bound regulatory approval framework. An appraisal of the international best practices divulges that technological backstopping, developing public-private partnerships, building institutional capacity for effective enforcement of regulatory regime and availability of information to farmers for selecting quality seed are equally vital for creating a well-functioning seed system in Pakistan.